2008
DOI: 10.1007/s11829-008-9029-4
|View full text |Cite
|
Sign up to set email alerts
|

Infestation by a Nalepella species induces emissions of α- and β-farnesenes, (−)-linalool and aromatic compounds in Norway spruce clones of different susceptibility to the large pine weevil

Abstract: The emissions of spruce grafts (Picea abies), caused by infestation of an acarid species of the genus Nalepella were investigated. Volatiles of three clones, both healthy and infested, with different susceptibility to the large pine weevil Hylobius abietis were collected by solid phase micro extraction (SPME) and analyzed by gas chromatograph coupled to mass-spectrometry (GC-MS). In addition, enantiomers of the main chiral compounds were separated by a two dimensional-gas chromatograph (2D-GC). In the characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 47 publications
3
19
0
Order By: Relevance
“…Feeding of Nalepella sp. mites on spruce induces release of (2)-linalool (Kännaste et al 2008). This suggests that (2)-linalool might be a general insect oviposition deterrent produced by larva-damaged foliage, although whether larvadamaged D. wrightii plants produce (2)-linalool remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding of Nalepella sp. mites on spruce induces release of (2)-linalool (Kännaste et al 2008). This suggests that (2)-linalool might be a general insect oviposition deterrent produced by larva-damaged foliage, although whether larvadamaged D. wrightii plants produce (2)-linalool remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that clones of small conifer plants infested by mites release many kinds of compounds, especially terpenes (Kännaste et al 2008). Arimura et al (2000a, b) showed that DMNT and (E)-β-ocimene released by bean plants attacked by the spider mite Tetranychus urticae activate genes involved in the induced defense reaction of intact plants.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we studied the response of Norway spruce clones with different resistance to the pine weevil [Hylobius abietis (L.)] to the attack of mites of Nalepella sp.. We found the infested spruces to release a flower-like scent, which is a very different from the emissions of healthy plants (Kännaste et al 2008). In the present study, we compared the volatile blends released by a Norway spruce clone infested either by Nalepella sp.…”
Section: Introductionmentioning
confidence: 99%
“…Although stressinduced emissions bursts have also been observed following enclosure installation (e.g., Arey et al, 1995), all enclosures were allowed to equilibrate prior to sampling for a minimum of 16 h to minimize this risk. Enclosure temperatures remained very close to ambient values for all trees sampled during this first visit, so heat stress was ruled out as a cause of the unusual emissions observed from CT1, which also emitted methyl salicylate as its dominant OVOC during the first sampling period (unlike any other tree sampled), a compound whose emissions are known to be enhanced in many tree species in response to both biotic and abiotic stressors (e.g., Kännaste et al, 2008;Joó et al, 2011). This tree also emitted ∼ 30-50 times more o-cymene and p-cymenene than any of the other trees sampled (data not shown) and had unusual behavior in both MT and SQT profiles through the course of the growing season.…”
Section: Biogeosciencesmentioning
confidence: 96%